Implementation of Healthy Housing Standard in Kandri Village, Gunung Pati - Isna Pratiwi; Dimas Indra Yulianto Alimuddin; Dimas Wicaksono; Fitri Dwi Indarti (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2025)
Poverty is a social phenomenon almost as old as the age of human civilization. Poverty and welfare are likened to two sides of a coin that are inseparable from how good the country's government is. Poverty indicators are generally caused by limited access to public services, the difficulty of accessing and receiving health services, the difficulty of getting easy access to information, and so on. Thus, the involvement of the bureaucracy, namely the government, is important because the problem of Poverty is the state's responsibility as the holder of government. The problem of Poverty is a complex problem that must be handled comprehensively across sectors, continuously and synergistically. This is because the problem of Poverty is the source and development of social problems, one of which is uninhabitable housing; therefore, Poverty must be handled seriously by both the government and society. The purpose of this event is to educate and help level the development of healthy and habitable houses, especially for the community in Kandri Village, Gunung Pati. This study enables researchers to gather objective data by identifying and characterizing current events through a qualitative approach. Gunung Pati District boasts potential natural resources that can be developed for agriculture, fisheries, plantations, and nature tourism. However, parts of the Kandri Village still face economic disparities. This situation is exacerbated by limited infrastructure, such as damaged roads and inadequate drainage, resulting in uneven development. Therefore, the Semarang City Government is implementing the Healthy and Livable Homes (Ruslani) program, which involves outreach, implementation, monitoring, and evaluation.